(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The study sought to determine the impact of intellectual capital in achieving competitive advantage (a survey of the opinions of workers in the Maysan Oil Company (a public company), it is known that each company has intellectual capital that contains three basic dimensions (human capital, customer capital, capital Structural) and since the competitive advantage is framed in the company’s ability to achieve its goals, this depends on its ability to produce products that meet the requirements of customers, and given the limited studies that dealt with the relationship of correlation and impact on intellectual capital and the achievement of competitive advantage in the company (within the limits of the researcher’s knowledge), the researcher sought To contain his current study of these two variables within a comprehensive framework in an attempt to study the relationship of correlation and effect between them In general, the study tries to answer the following questions: 1- Is there a clear perception among the employees of the researched company about the two issues of intellectual capital and competitive advantage? 2-Is there an increase in the awareness of the employees in the company under study of the concept of intellectual capital and competitive advantage? The study reached a number of conclusions, the most important of which are: 1-There is a significant correlation between intellectual capital and competitive advantage in the company under study 2-There is a significant effect between intellectual capital and competitive advantage at the level of the company under study.